2016
DOI: 10.1080/2162402x.2016.1234571
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming the lung microenvironment by inhaled immunotherapy fosters immune destruction of tumor

Abstract: Due to their constant exposure to inhaled antigens, lungs represent a particularly immunosuppressive environment that limits excessive immune responses; however, cancer cells can exploit this unique environment for their growth. We previously described the ability of aerosolized CpG-ODN combined with Poly(I:C) (TLR9 and TLR3 agonists, respectively) to promote antitumor immunity in a B16 melanoma lung metastasis model. Here, we explored the possibility of improving the therapeutic efficacy of TLR9/TLR3 agonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…A different CpG-ODN, delivered intratracheally, has been reported to have activity on lung tumors when formulated as a microparticle, but not as a solution (38). In a model of B16 melanoma lung metastasis, an inhaled formulation of poly (I:C) TLR3 agonist and CpG-ODN TLR9 agonist was shown to decrease lung metastasis restoring NK-cell effector function (39).…”
Section: Discussionmentioning
confidence: 99%
“…A different CpG-ODN, delivered intratracheally, has been reported to have activity on lung tumors when formulated as a microparticle, but not as a solution (38). In a model of B16 melanoma lung metastasis, an inhaled formulation of poly (I:C) TLR3 agonist and CpG-ODN TLR9 agonist was shown to decrease lung metastasis restoring NK-cell effector function (39).…”
Section: Discussionmentioning
confidence: 99%
“…We previously observed that the aerosol delivery of various agents, such as TLR agonists and cytokines, was able to favor the immune-mediated control of experimental lung metastases, indicating the feasibility of influencing local lung immunity through a non-invasive strategy [63][64][65][66][67].…”
Section: Lung Microbiota and Cancermentioning
confidence: 99%
“…Since the submission of the latest Trial Watch dealing with this topic (September 2015), 88 no less than 66 clinical studies involving the administration of TLR agonists to cancer patients have been initiated (source http://clinicaltrials.gov/). The majority of these trials involve the FDA-approved molecules imiquimod (17 studies) and BCG (11 studies), as well as the hitherto experimental TLR3 agonist HiltonolÂź, a particular formulation of polyI:C that includes carboxymethylcellulose and poly-L-lysine as stabilizing agents, 156,167,168 (20 studies), and the TLR9 agonist SD-101 (9 studies) ( Table 1).…”
Section: Recently Initiated Clinical Trialsmentioning
confidence: 99%